2022
DOI: 10.1136/jitc-2021-004219
|View full text |Cite
|
Sign up to set email alerts
|

Tumor-associated macrophage-specific CD155 contributes to M2-phenotype transition, immunosuppression, and tumor progression in colorectal cancer

Abstract: BackgroundOnco-immunogenic molecule CD155 is overexpressed in various tumor microenvironments (TME) including in colorectal cancer (CRC). Tumor-associated macrophages (TAMs) are the most abundant immune cells in CRC TME and play a vital role in CRC progression and metastasis. Most studies have focused on investigating the role of CRC cell-specific CD155 on CRC progression, while the contribution of TAMs-specific CD155 is still unknown. Here, we sought to investigate the expression pattern of CD155 in CRC TAMs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(21 citation statements)
references
References 48 publications
1
20
0
Order By: Relevance
“…The majority of CRCs with TME are immunosuppressed, and the pMMR type, which accounts for 85% of CRCs, lacks response to treatment with immune checkpoint inhibitors (ICIs) 25–27 . Studies have confirmed that the dMMR phenotype with sustained response to ICIs is characterized by a high tumor mutational burden (TMB), with a more than 100-fold increase in mutation rates in the dMMR phenotype compared with pMMR tumors 28 .…”
Section: Discussionmentioning
confidence: 99%
“…The majority of CRCs with TME are immunosuppressed, and the pMMR type, which accounts for 85% of CRCs, lacks response to treatment with immune checkpoint inhibitors (ICIs) 25–27 . Studies have confirmed that the dMMR phenotype with sustained response to ICIs is characterized by a high tumor mutational burden (TMB), with a more than 100-fold increase in mutation rates in the dMMR phenotype compared with pMMR tumors 28 .…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study, an increased number of CD155+ TAMs were found in clinical CRC samples. These CD155+ TAMs were supporting cancer cell migration and invasion through a TGFβ/STAT3-dependent release of matrix metalloproteinases (MMP) 2 and 9 [ 39 ].…”
Section: Tgfβ As a Regulator Of The Tumor Microenvironment In Crcmentioning
confidence: 99%
“…M2-like is one of the polarizations that dominate and promote tissue remodeling, wound healing, accelerate cellular proliferation, thereby eliminating the in ammatory response and restoring homeostasis in the organism [7] . M2-like TAMs are highly in ltrative and are associated with immunosuppression and malignancy [8] , previous studies have found that TAMs can attract immunosuppressive cells to the tumor site via the elevation of a variety of chemokines, cytokines and induce PD-L1 expression, which attenuated cellular immunity by inhibiting the proliferation of CD8 + T cells [9,10] .…”
Section: Introductionmentioning
confidence: 99%